ANALISIS GELOMBANG PASANG TERHADAP BANGUNAN GROIN TIPE I (STUDI KASUS PANTAI KOTA PADANG) - Nadita, Dwiki; Besperi, Besperi; Gunawan, Gusta (Inersia: Jurnal Teknik Sipil, 2019)
Pantai Kota Padang had a breakwater (groin) which serves to withstand sedimentation transport, but building has been damaged and deformed. The purpose of this study was to analyze the building of form I groin using dolos material at Pantai Kota Padang. The method of conducting research primary data processing method used in field direct namely collection (Hs and Ts), while secondary data analysis method using wind data, and analysis data tides. Secondary data in this in this research is the wind data taken for ten years (2009 - 2018) obtained from the Badan Meteorologi Klimatologi dan Geofisika (BMKG) Maritim Teluk Bayur and the tides data taken during the last 5 years (2014-2018) whom obtained from PT. Pelabuhan Indonesia II Teluk Bayur. Results of the groin dolos have 60,803 m in length, 2,20 m on water level, 4,875 m elevation lighthouse and 8,875 m elevation of building, peak width of 1,433 m on the arms building. Weight unit protective cover dolos groin arms are W=0,261 tons, W/10=21,6 kg, W/200=1,3 kg, and amount each layer is 5 m2 as many as 16 pieces for the arms building.Keywords: Breakwater, Groin, Dolos